A matter of dispute morality, democracy, and law - Peters, Christopher J. (New York ; Oxford : Oxford University Press, 2011)
Law often purports to require people, including government officials, to act in ways they think are morally wrong or harmful. What is it about law that can justify such a claim? This book offers an answer to this problem of law's authority.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Rule of law -- Philosophy; Law -- Moral and ethical aspects; Dispute resolution (Law) -- Moral and ethical aspects; Democracy; Constitutional law -- Moral and ethical aspects